ANALISIS EFEKTIVITAS TRANSPORMASI PEPAJAKAN DIGITAL DENGAN PENDEKATAN ORGANIZATIONAL CULTURE DAN TECHNOLOGY CONTEXT PADA UMKM DI KOTA MEDAN - Junawan Junawan; Sumardi Adiman (NUSANTARA : Jurnal Ilmu Pengetahuan Sosial, 2023)
This study aims to examine and analyze the effect of the effectiveness of using digital tax transformation using an organizational culture and technology context approach. The population of this study includes a portion of the assisted SMEs of the North Sumatra Regional Office, amounting to 40 SMEs, and uses a saturated sample technique. Data analysis using multiple linear regression. The results of the study show that simultaneously organization culture and technology context have a significant effect on the effectiveness of the use of tax digitalization. Partially, the organization culture and technology context have a significant positive effect on the effectiveness of the use of tax digitalization..